Integration of rCF in resin transfer pressing process. (May 2020) - Goergen, C; May, D; Mitschang, P
A new composite manufacturing process, resin transfer pressing, is introduced in this paper. In this process, nonwoven fabrics made of recycled carbon fibers are oversaturated with thermoset resin, i.e. they contain excess resin. The oversaturated nonwoven fabrics are prefabricated and used as resin carrier in a press process, where they are placed in a heated mold together with a dry textile-based preform. During pressing, the resin is pressed out and transferred from the nonwoven into the non-impregnated preform and hence impregnates the whole reinforcement. This study examines the oversaturation of nonwoven fabrics, the resin transfer pressing laminate manufacturing and the surface quality of the laminates. The ability of a nonwoven fabric to be oversaturated with resin is defined by the saturation degree, which was determined as up to 12 for glass fiber nonwoven fabrics and up to 60 for recycled carbon fiber nonwoven fabrics. Different laminates are manufactured by resin transfer pressing, and the impregnation quality is evaluated. With an optimized stacking sequence, a pore content <1% was achieved. The use of recycled carbon fiber nonwovens in the resin transfer pressing process leads to a less wavy surface compared to a wet compression molding manufactured laminate, showing a decrease of waviness Wz 25 of 11% minimum.